2014
DOI: 10.3390/molecules19055863
|View full text |Cite
|
Sign up to set email alerts
|

Norditerpenoids from Flickingeria fimbriata and Their Inhibitory Activities on Nitric Oxide and Tumor Necrosis Factor-α Production in Mouse Macrophages

Abstract: Bioassay-guided fractionation of the ethanolic extract of the leaves of Flickingeria flimbriata led to the isolation of two new degraded diterpenoids 1 and 2, a new ent-pimarane type diterpenoid 3, and four known steroids 4-7. The structures of 1-3 were elucidated by spectroscopic analysis, and their absolute configurations were determined by chemical methods, TDDFT quantum chemical calculations of ECD spectra, and CD exiton chirality method. Compounds 1 and 2, named flickinflimilins A and B, possess a rare 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…Analytical NMR and MS data indicated that the structure of 4 is stigmastane 3β,5α,6β-triol. The NMR data are in good agreement with reported values [7] (table 1).…”
Section: Resultssupporting
confidence: 91%
“…Analytical NMR and MS data indicated that the structure of 4 is stigmastane 3β,5α,6β-triol. The NMR data are in good agreement with reported values [7] (table 1).…”
Section: Resultssupporting
confidence: 91%
“…Analysis of its NMR spectroscopic data (Tables 1 and 2) indicated high structural similarity with the known flickinflimilin B (Chen et al, 2014b), except that the keto function at C-7 position of flickinflimilin B was replaced by a sp 3 methine carbon in 6. This variation was confirmed by the pivotal HMBC correlation from H-14 [d H 6.87 (1H, d, J = 1.3 Hz)] to C-7 (d C 30.2) in 6.…”
Section: Structure Elucidation and Identificationmentioning
confidence: 93%
“…It is well known as an effective succedaneum for the precious and scarce congener Dendrobium candidum for treatment of inflammatory diseases, such as pneumonia, tuberculosis, bronchitis, asthma and pleurisy (Song, 1999). In a continuing search for bioactive metabolites from F. fimbriata (Chen et al, 2014a(Chen et al, , 2014b, five new norditerpenoids (1)(2)(3)(4)(5) representing rare examples of 16-nor-ent-pimaranes, two new dinorditerpenoids (6-7) possessing a skeleton of 15,16-dinor-entpimarane, and one new ent-pimarane diterpenoid glycoside (11), along with eight known analogs (8-10 and 12-16) were isolated. Their structures, including absolute configurations, were determined on the basis of detailed spectroscopic analysis and various forms of chemical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this medicinal plant (also named “You Gua Shi Hu”) was often used as the equivalent of Pale Ephemerantha (“Shi Hu”) in the medicinal market. Previous chemical investigations of this plant obtained pimarane-type diterpenoids, several phenanthrenes, steroids, and bibenzyls 7 8 9 10 11 12 . During our ongoing search of new bioactive secondary metabolites from herbal medicines 13 14 15 , we initiated the chemical study of this medicinal plant collected from Hainan province.…”
mentioning
confidence: 97%